Astrocytes and extracellular matrix in extrasynaptic volume transmission - Vargová, Lýdia; Syková, Eva (Philosophical transactions of the Royal Society of London. Series B, Biological sciences, 2014)
Volume transmission is a form of intercellular communication that does not require synapses; it is based on the diffusion of neuroactive substances across the brain extracellular space (ECS) and their binding to extrasynaptic high-affinity receptors on neurons or glia. Extracellular diffusion is restricted by the limited volume of the ECS, which is described by the ECS volume fraction α, and the presence of diffusion barriers, reflected by tortuosity λ, that are created, for example, by fine astrocytic processes or extracellular matrix (ECM) molecules. Organized astrocytic processes, ECM scaffolds or myelin sheets channel the extracellular diffusion so that it is facilitated in a certain direction, i.e. anisotropic. The diffusion properties of the ECS are profoundly influenced by various processes such as the swelling and morphological rebuilding of astrocytes during either transient or persisting physiological or pathological states, or the remodelling of the ECM in tumorous or epileptogenic tissue, during Alzheimer's disease, after enzymatic treatment or in transgenic animals. The changing diffusion properties of the ECM influence neuron-glia interaction, learning abilities, the extent of neuronal damage and even cell migration. From a clinical point of view, diffusion parameter changes occurring during pathological states could be important for diagnosis, drug delivery and treatment.
Keywords: Synaptic Transmission; Anisotropy; Cell Communication; Diffusion; Astrocytes; extracellular space; difuze; volume fraction; tortuosity; nervový přenos; extracelulární matrix; astrocytes; Animals; lidé; Humans; anizotropie; zvířata; Extracellular Matrix; astrocyty; extracellular matrix; mezibuněčná komunikace; diffusion